Draft and Fuel Requirements Measurement Using Tractor On-Board Data Acquisition System - Wan Ismail, Wan Ishak; Burkhardt, T. H. (Universiti Putra Malaysia Press, 1993)
The implement draw bar power requirement or draft is an important factor to determine tractor and machinery selection in machinery management. The implement draft is used to determine the fuel consumed for an operation. The tractor on-board data acquisition system was developed to ease in field data collection using the established equations from the ASAE standards.